Called to Serve : A History of Nuns in America - McGuinness, Margaret M. (Book collections on Project MUSE., 2013)
For many Americans, nuns and sisters are the face of the Catholic Church. Far more visible than priests, Catholic women religious teach at schools, found hospitals, offer food to the poor, and minister to those in need. Their work has shaped the American Catholic Church throughout its history. The author provides the reader with an overview of the history of Catholic women religious in American life, from the colonial period to the twenty-first century.